The effect of ventilation tube insertion or trans-tympanic silicone plug insertion on a patulous Eustachian tube. (2nd June 2016) - Endo, Shiori; Mizuta, Kunihiro; Takahashi, Goro; Nakanishi, Hiroshi; Yamatodani, Takashi; Misawa, Kiyoshi; Hosokawa, Seiji; Mineta, Hiroyuki
Abstract: Conclusions This study suggests that long-term ventilation tube insertion is the first-choice surgical treatment for a 'sniff-type' patulous Eustachian tube (PET). When treating a refractory PET, it is important to determine whether the patient had a habitual sniff.Objectives PET patients were divided into two groups: patients with a habitual sniff (sniff-type PET) and those without a habitual sniff (non-sniff-type PET). This study examined the effects of ventilation tube insertion or silicone plug insertion in each group.Methods Surgical procedures such as ventilation tube insertion or trans-tympanic silicone plug insertion were performed for these patients. Tubotympanoaero-dynamic graphy (TTAG) was also performed to determine the mechanisms underlying these treatments.Results There were 11 cases (17 ears) of sniff-type PET and 20 cases (27 ears) of non-sniff-type PET. An improvement in symptoms was found in 72.7% of the patients who underwent silicone plug insertion (66.7% for sniff-type PET and 74.1% for non-sniff-type PET) and in 90.9% of the patients who underwent ventilation tube insertion for sniff-type PET. In TTAG assessments, many sniff-type PET patients showed significant synchronous changes at high levels of pressure (over 40 daPa) in the external auditory meatus and nasopharynx when performing a slight Valsalva manoeuvre (below 200 daPa).